Analisis Hukum Perdata terhadap Keabsahan dan Pembuktian Tanda Tangan Digital Serta Pertanggungjawaban Platform E-Wallet dalam Transaksi E-Commerce - As-Sifa Pebrianti; Ardhita Aulia Utari; Salwa Fauziyah Anwar; Shabrina Najla Ingga Jayasti (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
The rapid development of digital technology has significantly transformed financial transactions in Indonesia, particularly through the growing use of e-wallets as practical and efficient payment tools. In a country with a Muslim-majority population, ensuring that e-wallet services comply with Islamic principles—free from riba, gharar, and maysir—is essential. This study aims to analyze Indonesia’s legal politics in regulating the use of e-wallets within the Islamic financial system and to assess their alignment with sharia principles. This research employs a normative juridical method with a qualitative descriptive approach by examining laws, regulations, and fatwas related to sharia-based fintech. The findings indicate that the Indonesian regulatory framework—through the OJK, Bank Indonesia, and DSN-MUI—has attempted to harmonize policies to support sharia-compliant digital financial services. However, several challenges remain, including limited e-wallet platforms with sharia certification, low digital sharia literacy among users, and the absence of detailed technical regulations specific to sharia e-wallet operations. This study recommends strengthening regulatory guidelines, increasing public literacy, and enhancing collaboration between regulators and the fintech industry to promote the development of sharia-compliant e-wallets that are secure, innovative, and aligned with Islamic financial principles.